Differential scanning calorimetry: An invaluable tool for a detailed thermodynamic characterization of macromolecules and their interactions - Michael H Chiu; Elmar J Prenner (Wolters Kluwer Medknow Publications, 2011)
Differential Scanning Calorimetry (DSC) is a highly sensitive technique to study the thermotropic properties of many different biological macromolecules and extracts. Since its early development, DSC has been applied to the pharmaceutical field with excipient studies and DNA drugs. In recent times, more attention has been applied to lipid-based drug delivery systems and drug interactions with biomimetic membranes. Highly reproducible phase transitions have been used to determine values, such as, the type of binding interaction, purity, stability, and release from a drug delivery mechanism. This review focuses on the use of DSC for biochemical and pharmaceutical applications.